Effects of Irsogladine on P450-isoform Specific Activities in Human Hepatic Microsomes - Nakamura, Akio; Tougou, Katsuhiko; Kitazumi, Hiroko; Yamada, Tetsuhiro; Honjou, Kumiko; Nonaka, Kiyoko; Mukai, Hideya (Arzneimittelforschung, 2006)
The effects of irsogladine (CAS 84504-69-8) on P450-isoform specific activities in human hepatic microsomes were examined. Irsogladine had little effects on coumarin hydroxylation (CYP2A6), 7-benzyl-oxyresorufin O-debenzylation (CYP2B6), S-mephenytoin hydroxylation (CYP2C19), bufuralol hydroxylation (CYP2D6), chlorzoxazone hydroxylation (CYP2E1) and nifedipine oxidation (CYP3A4) at concentrations ranging from 10 to 50 µmol/L. However, it inhibited 7-ethoxyresorufin O-deethylation (CYP1A2) and tolbutamide hydroxylation (CYP2C9) with the Ki values of 276 and 156 µmol/L, respectively. This suggests that it is a weak inhibitor of these isoforms. Because the plasma concentrations of irsogladine in humans are much lower than these Ki values, it is unlikely that irsogladine causes drug interactions with other drugs.
Keywords: Anti-ulcer agents; CAS 84504-69-8; Irsogladine, drug interaction, human hepatic microsomes, P450 inhibition